Copper-catalyzed reaction of aziridine for the synthesis of substituted imidazolidine and imidazolidinone - Hashimoto, Kota; Higuchi, Daiki; Matsubara, Satoshi; Murakami, Kei (Frontiers in Chemistry, 2023)
Herein we report a copper-catalyzed synthesis of imidazolidine by employing the reaction of aziridine with imine. The reaction smoothly provided a diverse range of 2-substituted imidazolidines with high compatibility with various functional groups. Moreover, during our investigation, we discovered that isocyanate also reacted with aziridine to yield substituted imidazolidinones efficiently. The versatility of these reactions was further demonstrated by their application in the synthesis of hybrid molecules derived from two pharmaceutical compounds. This approach opens new possibilities for the discovery of novel classes of bioactive molecules.